A Pseudo-Private Library (L7, A)? Investigations on the “House of the Roman Scribes” - Nikola Bellucci (Gerión, 2016)
The Syrian city of Dura Europos, surprising for its exceptional architectural sense of re-use and for its multi-ethnicity due to the different domains, offers unique cases of construction, particularly affected by the last Roman domination before the fall. The survey focuses on the main house of the block L7, the domus A, also known as the “house of the Romans scribes”, considering his structure and the discoveries, both in view of the Roman that of the Sassanid occupation and inserting it in the context of the others domus of the city. The possibility that the property was managed by high-ranking military has finally allowed a connection with the literary papyri of Dura coming precisely from this same block.